How damaging is imprisonment in the long-term? A controlled experiment comparing long-term effects of community service and short custodial sentences on re-offending and social integration - Killias, Martin; Gilliéron, Gwladys; Villard, Françoise; Poglia, Clara (Journal of experimental criminology, 2010)
Since the 19th century, short custodial sentences were said to foster re-offending through alienating inmates from families and work. The present study is one of the few randomized controlled trials comparing short custodial sentences with community service orders. Between 1993 and 1995, 123 subjects were randomly assigned to community service or immediate custody (of a maximum of 14 days) in the Lake of Geneva area (Switzerland). The present study updates results published earlier on a follow-up period of 2 years by considering re-convictions and social integration over 11 years. Although statistically not significant, re-offending was tentatively more common among ex-prisoners in the long run. Eleven years later, ex-prisoners were better off, complied better with tax regulations, and did not fare worse regarding employment history or marital status. In line with recent systematic reviews, the results do not confirm the wide-spread assumption that short custodial sanctions are harmful when compared to community service.